Modus ponens is stated $$((P \implies Q) \land P) \implies Q$$ But isn't $(P \implies Q) = (\lnot P \lor Q)$?

Then we get $((P \implies Q) \land P) \implies Q$ $= (\lnot P \lor Q) \land P$ $= (\lnot P \land P) \lor (P \land Q)$ $= \text{False} \lor (P \land Q)$ $= P \land Q$ So $P\land Q$, not just $Q$. Why do we say that modus ponens then just implies $Q$?

  • $\begingroup$ It also implies $P\wedge Q\wedge True$, but we don't say that either. $\endgroup$ – vadim123 Mar 11 '18 at 5:11
  • $\begingroup$ We say that it implies $Q$, not that it implies only $Q$. $\endgroup$ – Alexander Burstein Mar 11 '18 at 5:11
  • 1
    $\begingroup$ $P\implies (P\land Q)$ is equivalent to $P\implies Q$. “If this is a ruby, then it is red” is equivalent to “If this is a ruby, then it is red and it is a ruby”. $\endgroup$ – MJD Mar 11 '18 at 5:13

Yes, indeed, $P$ and $Q$ are both implied by $P$ and $P\to Q$.   In fact, $P$ and $Q$ and $P\to Q$ are all implied by $P$ and $P\to Q$.

However, we're most interested in learning new things.   $Q$ is new thing we learn from knowing $P$ and $P\to Q$.   It is not the only thing, but it is the new thing.

It is useful to know this, so we give the rule of inference a special name: "modus ponens".


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.